Effects of Norepinephrine and Cardiotrophin-1 on Phospholipase D Activity and Incorporation of Myristic Acid Into Phosphatidylcholine in Rat Heart - Tobias Weismüller; Jochen Klein; Konrad Löffelholz (Elsevier, 2004)
The present study is part of a project on phospholipase D (PLD) in cardiac hypertrophy and analyzed effects on PLD activity of two growth stimuli, norepinephrine (NE) and cardiotrophin-1 (CT-1), in incubated rat heart. Phosphatidylcholine (PC) was labeled by 3H-myristic acid. PLD produced 3H-phosphatidylethanol (3H-PEth) from 3H-PC in the presence of ethanol and maintained a basal formation of 3H-PEth. Short-term and long-term exposure to NE for 2 or 13 h, respectively, enhanced the formation of 3H-PEth, which was blocked by prazosin. Long-term pretreatment with NE or CT-1 increased the incorporation of 3H-myristic acid into PC, which was blocked by atenolol. When the 3H-PEth formation was expressed as a fraction of 3H-PC, PLD activity seemingly was unchanged (NE) or markedly reduced (CT-1); the true effects, namely, stimulation by NE and nonresponsiveness towards CT-1, were unraveled by atenolol (NE) or when PLD activity was expressed as 3H-PEth per ng protein. In conclusion, α-adrenoceptor activation increased PLD activity. Long-term treatment with NE (via β-receptors) or CT-1 enhanced the 3H-myristic acid incorporation into a PC compartment, that was not available for the α-receptor-mediated PLD activation. These results were discussed in regard to cellular mechanisms of cardiac hypertrophy and to the transphosphatidylation assay of PLD. Keywords:: phosphatidylcholine, phospholipase D, transphosphatidylation assay, adrenoceptor, heart